Tanggung Jawab Notaris Dalam Pembetulan Kesalahan Tulis Atau Ketik Yang Terdapat Pada Akta Yang Telah Ditandatangani - Ni Kadek Arisya Citra Repinta; I Nyoman Putu Budiartha; Anak Agung Istri Agung (Jurnal Preferensi Hukum, 2025)
From "Law No. 2 of 2014 concerning Amendments to Law No. 30 of 2004 concerning the Position of Notary, it gives authority to notaries to make authentic deeds related to all acts, agreements, and determinations required by existing regulations". The problem that the researcher took from the thesis is the potential for the deed made by the notary that in carrying out the authority of the notary to make a typographical error in the minutes of the deed and a notary is a public official who has the authority to make an authentic deed and has the potential to make an error, this error requires the notary's responsibility to resolve the typographical error. This study is of the normative legal type and has a Statute Approach & conceptual approach. Corrections are made to witnesses, appearing parties and notaries, which are then recorded in the minutes of correction. The notary's authority includes correcting written or typographical errors in the minutes of the deed that have been signed. The notary's obligation to make typographical errors in the minutes of the deed that have been copied is carried out by means of renvoi or correcting the wrong copy of the minutes of the deed and initialed by the notary.